Telemedicine: An Evolving Field in Hepatology - Piao, Cindy (Hepatol Commun, 2019)
Healthcare delivery has been dramatically changing in recent times with advances in technology. One area of expansion has been the use of telemedicine due to progression in communication technologies. Telemedicine offers the opportunity to overcome barriers of access, improve patient satisfaction, improve healthcare outcomes and streamline communication between patients and providers. The primary modalities of telemedicine can be grouped into categories of ‘remote monitoring,’ ‘store and forward’ and ‘interactive telemedicine.’ These modalities of telemedicine have been practiced and explored within the scope of hepatology such as in liver transplantation, hepatocellular carcinoma and management of chronic hepatitis C (CHC). There are numerous telemedicine‐based CHC management studies and programs that have developed in New Mexico, the Department of Veterans Affairs, as well as globally in Australia and Canada. In Northern California, the University of New Mexico telemedicine‐based model of ‘ECHO’ has been extended to develop community‐based champions to screen‐link‐treat CHC patients with the goal to eliminate hepatitis C. Despite the advantages to telemedicine, there are still many barriers to seamless integration due to reimbursement and up‐front cost. Nevertheless, it remains an essential part in providing world‐class care to liver patients across geographic and economic barriers.